Reis naar het Einde van het Atelier : Tachtig Reizen Tachtig Ateliers. - Lokaal 01, Breda (Breda : Lokaal 01, 1992)
Claassen, Tom ; van der Grijn, Max ; van den Ban, Hans ; Benson, Simon ; Besemer, Theo ; Hamersma, Gerlof ; Leyten, Emil ; van Meeuwen, Hans ; van Westing, Albert ; Bagen, Arthur ; et al.
Reis naar het Einde van het Atelier, Lokaal 01, Breda, 18-11-1992 / 20-12-1992
kunstcatalogus